PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS ARTICULATE STORYLINE TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN SISWA KELAS IV SD NEGERI 7 LANGSA - Aprilianty, Ardhini; Fransyaigu, Ronald; Juliati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This problem is caused by the difficulty of fourth-grade students at SD Negeri 7 Langsa in understanding reading materials because the learning process still focuses on the use of printed books without the help of technology-based interactive learning media, and reading activities are carried out in turns. This study aims to determine the validity, feasibility, and effectiveness of the developed product. This study used the ADDIE Research and Development (R&D) model with data collection techniques in the form of observation, interviews, questionnaires, and tests. The validity of the subject matter experts was 82%, the measuring instruments was 94%, the language experts was 84%, and the media experts was 97.5% with the criteria ‘Very Appropriate’. The response rate from learning practitioners was 96.92% and from students was 83%, with a criterion of ‘Very Practical’. The effectiveness of Articulate Storyline-based interactive learning media was analysed using normality tests, paired sample t-tests, and N-Gain tests. The normality test results showed a pre-test value of 0.622 and a post-test value of 0.064, indicating that the data was normally distributed. The average score increased from 56.36 in the pre-test to 84.54 in the post-test with Sig. 2-tailed < 0.001, indicating a significant difference. The N-Gain score was 0.68, classified as ‘Moderate,’ and the percentage was 68%, classified as ‘Quite Effective.’ Based on the results described above, the Articulate Storyline-based interactive learning media is valid, practical, and effective in improving the reading comprehension skills of fourth-grade students.